Innovation, Ruptures and Economic Cycles in Technology Platforms: Proposition of an analytical framework - de Souza Ferreira, Wilquer Silvano; Vale, Gláucia Maria Vasconcellos; Bernardes, Patrícia (Organizações & Sociedade, 2021)
The world has been going through many technological transformations, which affect not only the productive systems, but also the prevailing social and institutional spheres, creating a fragmented and hard to understand scenario. Different theories aim at evaluating some specific dimensions of the complex process in course at the micro- meso- and macrolevels; however, none seems to encompass the multiple dimensions of the phenomenon concomitantly. To address such research gap, we resort to adaptive theory, which, on the one hand, turns to theoretical constructs on disruptive innovation, creative destruction and economic cycles; on the other, resorts to data and information on the emergence and proliferation of platforms for collaborative consumption. Our paper brings a unified theoretical conception, allowing a more comprehensive and integrated analysis of more than one dimension of the transformation process currently in course.